Toxic Megacolon Burdened with COVID-19 Coinfection-Worsening of an Unfavorable Diagnosis: A Single-Center Retrospective Study - Řezáč, Tomáš; Klos, Dušan; Stašek, Martin; Vrba, Radek; Zbořil, Pavel; Špička, Petr (Life (Basel, Switzerland), 2022)
INTRODUCTION: This study primarily sought to evaluate the risk factors for toxic megacolon development and treatment outcomes in Clostridium difficile-positive COVID-19 patients, secondarily to determining predictors of survival. METHODS: During the second COVID-19 wave (May 2020 to May 2021), we identified 645 patients with confirmed COVID-19 infection, including 160 patients with a severe course in the intensive care unit. We selected patients with Clostridium difficile infection (CDI) (31 patients) and patients with toxic megacolon (9 patients) and analyzed possible risk factors. RESULTS: Patients who developed toxic megacolon had a higher incidence (without statistical significance, due to small sample size) of cancer and chronic obstructive pulmonary disease, a higher proportion of them required antibiotic treatment using cephalosporins or penicillins, and there was a higher rate of extracorporeal circulation usage. C-reactive protein (CRP) and interleukin-6 values showed significant differences between the groups (CRP [median 126 mg/L in the non-toxic megacolon cohort and 237 mg/L in the toxic megacolon cohort; p = 0.037] and interleukin-6 [median 252 ng/L in the group without toxic megacolon and 1127 ng/L in those with toxic megacolon; p = 0.016]). As possible predictors of survival, age, presence of chronic venous insufficiency, cardiac disease, mechanical ventilation, and infection with Candida species were significant for increasing the risk of death, while corticosteroid and cephalosporin treatment and current Klebsiella infection decreased this risk. CONCLUSIONS: More than ever, the COVID-19 pandemic required strong up-to-date treatment recommendations to decrease the rate of serious in-hospital complications. Further studies are required to evaluate the interplay between COVID-19 and CDI/toxic megacolon.
Keywords: COVID-19 infection; prognosis; Clostridium difficile infection; toxic megacolon; Klebsiella species; Candida species